Te Pākeketanga: living and dying in advanced age - a study protocol. Issue 1 (December 2015) - Gott, Merryn; Moeke-Maxwell, Tess; Williams, Lisa; Black, Stella; Trussardi, Gabriella; Wiles, Janine; Mules, Rangimarie; Rolleston, Anna; Kerse, Ngaire
Abstract Background The number of people dying in advanced old age is increasing rapidly and building the evidence base regarding end - of - life care for older people has been identified as an international policy priority. The unique opportunity to link longitudinal studies of ageing with studies exploring the end of life circumstances of older people remains under-exploited internationally. Very little is known about the specific circumstances, cultural needs and care preferences of indigenous older people, including Māori, at end - of - life and the needs of their whānau/ extended family carers. Methods We will use rigorous qualitative methods to conduct post-bereavement interviews with bereaved whānau and family of 50–60 people who died >80 years; approximately half of participants will be Maori. The older decedents were participants in the first longitudinal study of older people involving a specific indigenous cohort internationally:Te Puāwaitanga O Ngā Tapuwae Kia Ora Tonu, Life and Living in Advanced Age: a Cohort Study in New Zealand (LiLACS NZ). Prior to death, they completed a questionnaire regarding their end-of-life preferences and nominated a family or whānau member to participate in this separate study exploring end-of-life circumstances of those in advanced age. Discussion Recommendations to improve care will be formulated in collaboration with participants and their local hapū (sub-tribe). Ultimately this study has the potential to inform better outcomes for the growing numbers of people dying in advanced old age both in New Zealand and internationally, as well as their whānau and family caregivers. It also highlights the ability to generate an in-depth understanding of end-of-life circumstances by appending studies of palliative and end-of-life care onto existing longitudinal studies.